2023
DOI: 10.1002/bse.3359
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐environmental employees and sustainable hospitality and tourism businesses: Exploring strategic reasons and global motives for green behaviors

Abstract: The promotion of low‐carbon lifestyles has led to increased emphasis on the sustainability of the hospitality and tourism industry and the pro‐environmental performance of employees in the workplace. This study examined the factors influencing the formation of employees' pro‐environmental decision‐making in the workplace by extending the traditional behavioral reasoning theory with global motives (attitude, subjective norm, and perceived behavioral control) and the norm‐activation model. The samples were hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
(270 reference statements)
0
4
0
Order By: Relevance
“…Researches have shown that subjective norms and behavioral attitude have high explanatory power for individual environmentally responsible behavior (Chi et al, 2023;Qiu et al, 2022;Xie et al, 2022). Based on TPB and previous empirical findings, we hypothesized the following.…”
Section: Organism-responsementioning
confidence: 94%
See 1 more Smart Citation
“…Researches have shown that subjective norms and behavioral attitude have high explanatory power for individual environmentally responsible behavior (Chi et al, 2023;Qiu et al, 2022;Xie et al, 2022). Based on TPB and previous empirical findings, we hypothesized the following.…”
Section: Organism-responsementioning
confidence: 94%
“…Researches have shown that subjective norms and behavioral attitude have high explanatory power for individual environmentally responsible behavior (Chi et al, 2023; Qiu et al, 2022; Xie et al, 2022). Based on TPB and previous empirical findings, we hypothesized the following.H1 Subjective norms have a positive impact on environmentally responsible behavior.H2 Behavioral attitude has a positive impact on environmentally responsible behavior.…”
Section: Theoretical Hypothesesmentioning
confidence: 99%
“…The TPB has also been integrated with other theories, like the norm‐activation model (Kim et al, 2018), behavioural reasoning theory (Chi et al, 2023), self‐determination theory (Amirkiaee & Evangelopoulos, 2018), technology acceptance model (Liang et al, 2019), value‐belief‐norm theory (Becker‐leifhold, 2018; Roos & Hahn, 2019) and social identity theory (McNeill & Venter, 2019) to offer a more comprehensive understanding of behaviours. Overall, the TPB has evolved to become a more nuanced and comprehensive model that can be applied to a broad range of behaviours and contexts.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…PMN is an important normative dimension, especially in this context, as it acts as a moral compass for individuals to enact or avoid specific behaviour. Individuals having higher PMN feel obligated to contribute to social development and engage in socially responsible behaviour (Chi et al, 2023; Song et al, 2023). Studies (Hawlitschek et al, 2018; Liang et al, 2019) confirmed the impact of social norms on adopting SC.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sin embargo, para lograr una educación ambiental efectiva, Heimlich y Ardoin (2008) señalan que, con el fin de animar a los estudiantes a ser más respetuosos con el medio ambiente, los académicos deben entender qué factores motivan el comportamiento. Stern y Dietz (1994), Al Zaidi et al (2023 y Chi et al (2023) explicaron que el comportamiento proambiental de las personas se guía no solo por normas personales basadas en valores altruistas hacia otros seres humanos, sino también por normas basadas en el interés propio y en el altruismo hacia otras especies no humanas (Awan y Khan, 2021; Rameezdeen et al, 2019). Asimismo, afirmaron que las normas personales egoístas y biosféricas se activan de igual manera que las normas personales altruistas dentro de la teoría de activación de normas (Stern y Dietz, 1994).…”
unclassified